DETERMINAN KEJADIAN ISPA PADA BAYI USIA ≤ 1 TAHUN - Utami, Utami; Kistimbar, Siti; Harni, Harni; Apsari, Duhita Dyah; Halimah, Andi (Ensiklopedia of Journal, 2024)
Immunization is one of the efforts made by the government in order to improve the health status of toddlers. With the aim of preventing the occurrence of some diseases can be prevented by immunization. Parents, health cadres, and health workers play a role in increasing the number of immunization visits. The purpose of this study was to determine the relationship between the role of parents, cadres, and health workers on toddler immunization visits to the Posyandu of the Serai Wangi Puskesmas working area, Talang Muandau District. This research design is cross sectional. This research was conducted at Puskesmas Serai Wangi with a population of 787 people. The sampling technique is using purposive sampling to a sample of 89 people. Data collection tools in this study used observation sheets and the results of the study were processed using a questionnaire that had been tested / validity. The results in this study found that there is a relationship between health workers (0.0,048 < 0.05) with immunization visits of toddlers and there is no relationship between the role of parents (0.526 > 0.05), health cadres (0.185 > 0.05). The suggestion of this study is that the health center can be an evaluation material for the Puskesmas, especially health workers involved in the MCH program to improve service efforts in the form of education related to the importance of utilizing Posyandu.Keywords: The role of parents, health cadres, health workers, immunization